ORMDL3 Promotes Angiogenesis in Chronic Asthma Through the ERK1/2/VEGF/MMP-9 Pathway - Zhen Ding; Fei Yu; Yan Sun; Ning Jiao; Lina Shi; Jinghong Wan; Qinghua Liu (Frontiers Media S.A., 2022)
AimAngiogenesis plays a vital role in airway remodeling in chronic asthma. ORMDL3 has been identified to be closely associated with the development of asthma remodeling. This study was to investigate the mechanism of ORMDL3 in angiogenesis of chronic asthma.MethodsBALB/c mice were divided into three groups, including an asthmatic group (group A), a budesonide-treated group (group B), and a normal control group (group C). Hematoxylin and eosin and Masson staining were used to evaluate the pathological changes. Angiogenesis in lung tissue was examined by CD31 staining. The changes of ORMDL3, ERK1/2, and angiogenesis-associated MMP-9 and Vascular endothelial growth factor (VEGF) expression were examined. Furthermore, ORMDL3, MMP-9, and VEGF mRNA and protein levels were examined after transfection in BEAS-2B cells with the ORMDL3-overexpressed lentiviral vector.ResultsCompared with the control group, asthmatic mice indicated more severe airway angiogenesis with increased ORMDL3, ERK1/2, MMP-9, and VEGF expression. Budesonide alleviated airway angiogenesis, and CD31 expression was positive with the levels of ORMDL3, MMP-9, and VEGF (P < 0.01). After successful transfection in BEAS-2B cells with the ORMDL3-overexpressing lentiviral vector, VEGF, and MMP-9 expression were activated in vitro (P < 0.01).ConclusionIn conclusion, our study provides novel evidence that ORMDL3 promotes angiogenesis through upregulating VEGF and MMP-9 in chronic asthma.